The Pollock-Krasner Foundation, Inc. : Millennium Report 1995-1999. - Bergman, Charles C.; Thaw, Eugene Victor; The Pollock-Krasner Foundation Inc., New York (New York : The Pollock-Krasner Foundation Inc., 1999)
Meller, Ingo ; Bigbee, Brett ; Isaacs, Henry ; Birkas, Istvan ; Etzold, Eckhard ; Haasz, Istvan ; Basu, Arpita ; Kogge, Robert ; Nonkouni, Fernand ; Beerman, John ; Page, Judith ; Connors, Patrick ; Gorman, Richard ; Cohem, Cora ; Heeks, Willy ; Rodrigo, Fernando ; Harrington, Susan ; Navarra, Doug ; Hambleton, Susan ; Grotfeldt, Virgil ; Hurson, Michael ; O'Hara, Morgan ; Schneemann, Carolee ; Long, Charles A. ; Qiu, Ping ; Attie, Shimon ; Ward, Nari ; Schnitger, Lara ; Rasdjarmrearnsook, Araya ; Pedrosa, Renata ; Wasko, Ryszard ; Kubinsky, Bohus & Monika ; Ingleby, Joseph ; Gonzalez, Ronald ; Glissow, Roy ; Heiremans, Ronny ; Armstead, Kenseth ; Drezner, Amy ; Suska, Cestmir ; Wells, Shan ; Dunn, Jane ; Nguyen-Ely, Darlene ; Frasconi, Antonio ; Goodnough, Robert ; Ginnever, Charles ; Rose, Herman ; Blaine, Nell ; Hultberg, John ; Mancora, Ernest
Engels
boek